2007
DOI: 10.1002/polb.21242
|View full text |Cite
|
Sign up to set email alerts
|

Free‐volume and crystallinity in low molecular weight poly(ethylene oxide)

Abstract: Positron annihilation lifetime spectroscopy (PALS), differential scanning calorimetry, X-ray diffraction, and polarized light optical microscopy were used to study six low molar mass poly(ethylene oxide) samples with average molar masses ranging from 1 3 10 3 to 10 3 10 3 g mol À1 . Dynamic light scattering was used to determine molar mass and polydispersity rigorously. Polymer samples with 70-95% crystallinity, which is an unusual range in PALS studies, were prepared by molten material quenching. The ortho-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 45 publications
2
12
0
2
Order By: Relevance
“…The TPU presents the typical segmented structure, with T g 1 associated with a soft segments amorphous phase, and T g 2 and T m as the thermal events of the rigid segments arrangement [27]. The semicrystalline copolymer showed a low T g , probably related to the polyethylene glycol PPG block, and a low T m related to the polyethylene glycol block [28]. Variable results were obtained from the replicate analysis of electrolytes and composites.…”
Section: Resultsmentioning
confidence: 85%
“…The TPU presents the typical segmented structure, with T g 1 associated with a soft segments amorphous phase, and T g 2 and T m as the thermal events of the rigid segments arrangement [27]. The semicrystalline copolymer showed a low T g , probably related to the polyethylene glycol PPG block, and a low T m related to the polyethylene glycol block [28]. Variable results were obtained from the replicate analysis of electrolytes and composites.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, Misheva et al [2000] report that the free positron decay component I 2 increases linearly with crystallinity and find that its value correlates linearly to Vickers microhardness (VMH) values, thereby deducing that τ 2 and VMH are both determined by the crystalline regions in UHMW PEs. Machado et al [2007] reported wide-angle x-ray diffraction (WAXD), DSC, and PALS studies of six poly(ethylene oxide) samples, spanning the molecular weight range 1 to 10 kg/mol. They found that X c increased from about 70% to an asymptotic value of about 94% when molecular weight increased above 3 kg/mol.…”
Section: Pals As a Probe For Free Volume In Semicrystalline Polymersmentioning
confidence: 99%
“…(12.2), also decreased to an asymptotic value above M = 3 kg/mol. Machado et al [2007] also noted that I 3 ∼ 22%, even for the samples with highest crystallinity, and hence conclude that o-Ps forms and annihilates in the crystalline as well as amorphous regions of the polymer. The authors present no data on T g for their polymers, but T m increases with molecular weight and then levels off at M > 3 kg/mol, and hence it is interesting to note that the decrease observed in τ 3 with molecular weight is reminiscent of a similar effect observed in polystyrenes [Yu et al, 1994] and associated with the increasingly large contribution of holes associated with chain ends in lower-molecular-weight samples.…”
Section: Pals As a Probe For Free Volume In Semicrystalline Polymersmentioning
confidence: 99%
“…9 A espectroscopia de aniquilação de pósitrons (EAP) é uma ferramenta versátil na detecção e monitoramento da evolução de defeitos do tipo vacâncias em sistemas sólidos, 10 com presença cada vez mais marcante no estudo de materiais poliméricos. 11,12 Compósitos poliméricos com nanotubos de carbono foram alvo de estudos recentes utilizando as técnicas de EAP. 9,13 Dentre essas técnicas, a espectroscopia de vida média do pósitron (EVMP) permite monitorar as dimensões e concentração de volumes livres (vacâncias) através da obtenção de parâmetros de tempos de vida médios (t) e intensidades relativas (I) de formação de espécies positrônicas, respectivamente.…”
Section: Introductionunclassified
“…11,12 Esta técnica permite acessar como a distribuição de volume livre evolui com a temperatura, por exemplo.…”
Section: Introductionunclassified